2020
DOI: 10.3389/fphar.2020.01118
|View full text |Cite
|
Sign up to set email alerts
|

Kaempferol Protects Blood Vessels From Damage Induced by Oxidative Stress and Inflammation in Association With the Nrf2/HO-1 Signaling Pathway

Abstract: Over recent years, an increasing number of studies have confirmed that the occurrence and development of vascular pathological changes are closely related to oxidative stress and the inflammatory response of the vascular endothelium. Kaempferol is the most common flavonoid compound found in fruits and vegetables. Our present research identified that kaempferol had the capability to protect the vascular endothelium in a mouse model of vascular injury and explored the specific mechanisms underlying these effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 33 publications
1
37
1
Order By: Relevance
“…Since KFL stimulates the Nrf2/HO-1/NQO1 pathway [ 20 ] ( Figure S1 ), we assessed whether KFL activates the Nrf2/HO-1/NQO1 pathway in ZEA-supplemented cells. Based on Western blotting and qRT-PCR, it was found that the proteins were significantly ( p < 0.05) upregulated in cells pre-treated with KFL, compared to cells treated with ZEA alone ( Figure 2 B and Figure 3 A).…”
Section: Resultsmentioning
confidence: 99%
“…Since KFL stimulates the Nrf2/HO-1/NQO1 pathway [ 20 ] ( Figure S1 ), we assessed whether KFL activates the Nrf2/HO-1/NQO1 pathway in ZEA-supplemented cells. Based on Western blotting and qRT-PCR, it was found that the proteins were significantly ( p < 0.05) upregulated in cells pre-treated with KFL, compared to cells treated with ZEA alone ( Figure 2 B and Figure 3 A).…”
Section: Resultsmentioning
confidence: 99%
“…What is more, quercetin inhibited glomerular mesangial cell proliferation and epithelial-mesenchymal transition in DN via reactivation of the Hippo pathway and inhibition of the TGF- β /PI3K/Akt pathway, respectively [ 57 , 58 ]. Kaempferol, a natural polyflavonol, also exhibits nephroprotective effects in addition to its antioxidant and anti-inflammatory properties [ 59 ]. Studies demonstrated that kaempferol plays vital nephroprotective roles associating with inhibiting oxidative stress, proinflammatory cytokines (TNF- α and IL-1 β ), and fibrosis in DN via inhibiting hyperglycemia-induced activation RhoA/Rho-kinase [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoids protect NO from inactivation and prevent eNOS uncoupling by: 1) directly scavenging superoxide anion and preventing peroxynitrite formation (54); 2) inhibiting reactive oxygen species (ROS)-producing enzymes such as NADPH oxidase, 5-lipoxygenase, cyclooxygenases (COX), myeloperoxidase, and xanthine oxidase; 3) stimulating antioxidant enzymes such as superoxide dismutase (SOD), catalase, and glutathione peroxidase (36,55); 4) increasing the activity of nuclear factor erythroid-2 related factor 2 (Nrf2) and up-regulating antioxidant enzymes such as NADPH:quinone oxidoreductase 1, hemeoxygenase-1, glutathione-S-transferase, and γ-glutamylcysteine ligase (56,57). In this context, several in vitro studies demonstrated the endothelium-dependency of flavonoid-induced relaxation of different vascular preparations (58).…”
Section: Flavonoids Protect Against Endothelial Dysfunctionmentioning
confidence: 99%